Galaxy Evolution in a Pilot Survey up to z=1 and CDM Halos - E. Giraud; J. Melnick; Q.-S. Gu; H. Quintana; F. Selman; I. Toledo; P. Zelaya (Advances in Astronomy)
We study spectral evolution of galaxies in a magnitude limited sample of 550 galaxies from z=1 down to z=0.3 on a pencil beam of ≈10′×10′. We concentrate on the large apparent cosmological structures along the line of sight, and we bin our individual galaxy spectra to obtain representative high S/N spectra based upon these structures. We divide the resulting average spectra in three groups to facilitate the analysis:galaxies with pure absorption line spectra, galaxies with emission lines and blue continua, and galaxies with emission lines and red continua. We revisit the question of downsizing in emission-line galaxies between z=0.9 and z=0.45 in our pencil-beam and find the following results: strong star formation in emission line galaxies, aging in emission line galaxies, and aging in absorption systems, are shifting from bright to faint systems as cosmological time increases. Each redshift bin is repopulated in new starbursts. Therefore at redshifts z⩽1 galaxy formation is downsizing both in luminosity and number density. Our observations indicate that at z⩽1 star formation and hierarchical structure formation of CDM halos are not in phase.